Viral latency and potential eradication of HIV-1. Issue 8 (August 2012) - Matreyek, Kenneth A; Oztop, Ilker; Freed, Eric O; Engelman, Alan
Keystone Symposium on Frontiers in HIV Pathogenesis, Therapy and Eradication Whistler, BC, Canada, 26–31 March 2012 Although HAART can suppress plasma viral loads to undetectable levels, individuals infected with HIV-1 harbor latent reservoirs of integrated proviruses that re-emerge upon the cessation of drug treatment. The 2012 Keystone Symposium on Frontiers in HIV Pathogenesis, Therapy and Eradication highlighted the current understanding of latent infection and new methods to activate and target these reservoirs for eradication. This report focuses on a select few aspects of the discussion, including the extent that ongoing replication might contribute to the persistent viral reservoir, recent advances in activating the expression of latent proviruses, progress in developing effective animal models and potential avenues to eradicate the cells that constitute the latent reservoir.